Assessing the Condition and Damage of a Stilt Wooden Home in an Area Prone to Floods - Hasmeddy, Nur Qamariah; Biton, Ara Billa; Chin, Avyda Tang Pei; Idek, Sirhajwan; Danil, Jovinia; Amin, Dayang Amidah; Khatijah, Dayang Siti (Future Science / FSH-PH Publications, 2024)
This study was intended to assess condition and damages of a stilt wooden house located in in Keningau, Sabah, in order to develop a proper home repair and restoration plan that can be scaled up to other houses of similar design in areas that are susceptible to flood and other environmental factors which can affect the structural integrity. The findings revealed that the chosen stilt wooden house has decayed severely that many parts of the house mainly the roof, the floors, the railing and stairs were in decrepit condition which could pose danger to the occupants. The results also implied that there were various factors that led to the condition of the house namely termite infestation and moist and weakened wood which could be due to the damaged zinc roof that caused rainwater to leak into the house, direct contact with floodwater and possibly leaky plumbing. A repair and restoration work was done by focusing on the parts of the house that needed immediate fix in order to ensure comfort and safety of the household. This study may shed more light on how to repair and restore as well as redesign wooden homes in order to be more resilient towards damaged caused by environmental variables.